Comparison of the Efficacy of Surgical Decompression Alone and Combined With Canine Adipose Tissue-Derived Stem Cell Transplantation in Dogs With Acute Thoracolumbar Disk Disease and Spinal Cord Injury - Bach, Fernando Swiech; Rebelatto, Carmen Lucia Kuniyoshi; Fracaro, Leticia; Senegaglia, Alexandra Cristina; Fragoso, Felipe Yukio Ishikawa; Daga, Debora Regina; Brofman, Paulo Roberto Slud; Pimpão, Claudia Turra; Engracia Filho, Jair Rodini; Montiani-Ferreira, Fabiano; Villanova, José Ademar (Frontiers in Veterinary Science, 2019)
Paraparesis and paraplegia are common conditions in dogs, most often caused by a disc herniation in the thoracolumbar spinal segments (T3-L3), which is a neurological emergency. Surgical decompression should be performed as soon as possible when spinal compression is revealed by myelography, computed tomography, or magnetic resonance imaging. Mesenchymal stem-cell therapy is a promising adjunct treatment for spinal cord injury. This study sought to compare the effects of surgical decompression alone and combined with an allogeneic transplantation of canine adipose tissue-derived mesenchymal stem cells (cAd-MSCs) in the treatment of dogs with acute paraplegia. Twenty-two adult dogs of different breeds with acute paraplegia resulting from a Hansen type I disc herniation in the thoracolumbar region (T3-L3) were evaluated using computed tomography. All dogs had grade IV or V lesions and underwent surgery within 7 days after symptom onset. They were randomly assigned into two groups, 11 dogs in each. The dogs in Group I underwent hemilaminectomy, and those in Group II underwent hemilaminectomy and cAd-MSC epidural transplantation. In both groups, all dogs with grade IV lesions recovered locomotion. The median locomotion recovery period was 7 days for Group II and 21 days for Group I, and this difference was statistically significant (p < 0.05). Moreover, the median length of hospitalization after the surgery was statistically different between the two groups (Group I, 4 days; Group II, 3 days; p < 0.05). There were no statistically significant between-group differences regarding the number of animals with grade IV or V lesions that recovered locomotion and nociception. In conclusion, compared with surgical decompression alone, the use of epidural cAd-MSC transplantation with surgical decompression may contribute to faster locomotor recovery in dogs with acute paraplegia and reduce the length of post-surgery hospitalization.